2005
DOI: 10.1111/j.1365-2249.2005.02958.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of classical complement activation attenuates liver ischaemia and reperfusion injury in a rat model

Abstract: SummaryActivation of the complement system contributes to the pathogenesis of ischaemia/reperfusion (I/R) injury. We evaluated inhibition of the classical pathway of complement using C1-inhibitor (C1-inh) in a model of 70% partial liver I/R injury in male Wistar rats ( n = = = = 35). C1-inh was administered at 100, 200 or 400 IU/kg bodyweight, 5 min before 60 min ischaemia (pre-I) or 5 min before 24 h reperfusion (end-I). One hundred IU/kg bodyweight significantly reduced the increase of plasma levels of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 44 publications
(47 reference statements)
2
45
2
2
Order By: Relevance
“…Previous studies have demonstrated the presence of complement in the ischemically injured liver, with complement deposition on hepatocytes and sinusoidal endothelial cells, cells that are reported to express low levels of complement regulatory proteins (12,45). We similarly demonstrated the presence of C3d on hepatocytes and the sinusoidal endothelium in wt lean and steatotic mice after I/R and after transplantation.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have demonstrated the presence of complement in the ischemically injured liver, with complement deposition on hepatocytes and sinusoidal endothelial cells, cells that are reported to express low levels of complement regulatory proteins (12,45). We similarly demonstrated the presence of C3d on hepatocytes and the sinusoidal endothelium in wt lean and steatotic mice after I/R and after transplantation.…”
Section: Discussionsupporting
confidence: 61%
“…[27][28][29][30] Moreover, C1INH limited leukocyte adhesion and neutrophil infiltration in a model of ischemia-reperfusion in the liver. [31][32][33] We observed that rhC1INH was very effective in limiting complement activation in renal tissue, as showed by the dramatic reduction of C4d and C5b-9 deposition. It is well known that early activation of complement leads to the release of active substances including C3a and C5a that can increase the recruitment of inflammatory cells.…”
Section: Discussionmentioning
confidence: 84%
“…The proposed mechanism of CRP involvement is through local activation of the complement cascade (39), and increased levels of CRP are reported to correlate with an increase in tissue injury after ischemia and reperfusion (3,13). Pharmacological inhibition of one or more of the multiple pathways of the inflammatory response has been demonstrated to reduce the extent of irreversible tissue injury after ischemia and reperfusion (15,36). Previous studies have shown that estrogen has the ability to reduce infarct size in the reperfused myocardium, possibly through modulation of the complement cascade, by reduction of CRP (5), or by an estrogen receptor-mediated anti-inflammatory mechanism (25,38).…”
mentioning
confidence: 99%